2017
DOI: 10.15171/ijoem.2017.913
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Auditory Pathway in Traffic Policemen

Abstract: Background: Traffic policemen working at heavy traffic junctions are continuously exposed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Bilateral and symmetrical hearing loss in traffic policemen with chronic noise exposure was reported in the study by Indora et al . [ 24 ] The study by Tikriwal et al . [ 35 ] among carpet workers observed a high prevalence of both tinnitus and hearing loss, with increasing prevalence associated with the greater severity of hearing loss.…”
Section: R Esultsmentioning
confidence: 99%
“…Bilateral and symmetrical hearing loss in traffic policemen with chronic noise exposure was reported in the study by Indora et al . [ 24 ] The study by Tikriwal et al . [ 35 ] among carpet workers observed a high prevalence of both tinnitus and hearing loss, with increasing prevalence associated with the greater severity of hearing loss.…”
Section: R Esultsmentioning
confidence: 99%
“…Earlier, we observed a conduction delay in the peripheral part of the auditory pathway in traffic policemen. [7] In addition to traffic noise, various other factors such as lack of awareness of protective measures and duration of exposure for more than the allotted hours may have contributed to the development of hearing impairment in them. Similarly, alteration in brainstem auditory evoked response indicating altered auditory conduction up to the level of the brainstem with no significant change in MLR and P300 response was observed in subjects exposed to noise at Mumbai Airport.…”
Section: Discussionmentioning
confidence: 99%
“…We have evaluated the possibility of deficits in auditory pathways in traffic policemen previously by means of brainstem evoked response audiometry, midlatency response (MLR) and slow vertex response. [7] Delayed conduction in the peripheral part of the auditory pathway was observed, while conduction was intact at the subcortical and cortical level.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have found a link between the length of hazardous noise exposure at work and the degree of hearing loss in workers [16,[36][37][38]. Indora et al discovered bilateral and symmetrical hearing loss in traffic cops exposed to chronic noise [17]. They discovered that chronic noise exposure resulted in delayed conduction in the peripheral part of the auditory pathway, ie, auditory nerve up to the level of the superior olivary nucleus; no impairment was observed at the level of sub-cortical, cortical, or association areas.…”
Section: [23]mentioning
confidence: 99%